TINGKAT PENERAPAN TEKNOLOGI BUDIDAYA PADI ORGANIK DI DESA LOMBOK KULON KECAMATAN WONOSARI KABUPATEN BONDOWOSO - Tanti Kustiari (UNEJ e-Proceeding)
The study aimed to analyze: (1) the level of organic rice cultivation technology, (2) the perception of farmers and institutional support organic farming, (3) the relationship of perception and institutional support organic farming with the level of organic rice cultivation technology. The study used survey method. The total sample of 34 respondents to the census sampling technique. The analytical method used is the description and correlation. The results of the study are (1) the level of organic rice cultivation technology in the optimal category. (2) a positive perception of farmers on organic rice cultivation technology technical or non-technical. (3) organic farming organizations supporting farmers to apply organic rice cultivation technology. (4) the perception of farmers associated with the level of organic rice cultivation technology, (5) institutional support organic farming relate to the level of organic rice cultivation technology. Organic rice cultivation Bondowoso Kulon village Lombok an organic rice production centers are very prospectively and can be used as a reference for the development of organic rice in other regions.